(x-2)/6=(x+3)/9

Simple and best practice solution for (x-2)/6=(x+3)/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)/6=(x+3)/9 equation:


x in (-oo:+oo)

(x-2)/6 = (x+3)/9 // - (x+3)/9

(x-2)/6-((x+3)/9) = 0

(x-2)/6+(-1*(x+3))/9 = 0

(9*(x-2))/(6*9)+(-1*6*(x+3))/(6*9) = 0

9*(x-2)-1*6*(x+3) = 0

3*x-36 = 0

(3*x-36)/(6*9) = 0

(3*x-36)/(6*9) = 0 // * 6*9

3*x-36 = 0

3*x-36 = 0 // + 36

3*x = 36 // : 3

x = 36/3

x = 12

x = 12

See similar equations:

| 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y | | 61-4x=10+19 |

Equations solver categories